Highly Efficient Perovskite–Perovskite Tandem Solar Cells Reaching 80% of the Theoretical Limit in Photovoltage - Rajagopal, Adharsh; Yang, Zhibin; Jo, Sae Byeok; Braly, Ian L.; Liang, Po‐Wei; Hillhouse, Hugh W.; Jen, Alex K.‐Y. (Advanced materials (Weinheim), 2017)
Organic–inorganic hybrid perovskite multijunction solar cells have immense potential to realize power conversion efficiencies (PCEs) beyond the Shockley–Queisser limit of single‐junction solar cells; however, they are limited by large nonideal photovoltage loss (V oc,loss) in small‐ and large‐bandgap subcells. Here, an integrated approach is utilized to improve the V oc of subcells with optimized bandgaps and fabricate perovskite–perovskite tandem solar cells with small V oc,loss. A fullerene variant, Indene‐C60 bis‐adduct, is used to achieve optimized interfacial contact in a small‐bandgap (≈1.2 eV) subcell, which facilitates higher quasi‐Fermi level splitting, reduces nonradiative recombination, alleviates hysteresis instabilities, and improves V oc to 0.84 V. Compositional engineering of large‐bandgap (≈1.8 eV) perovskite is employed to realize a subcell with a transparent top electrode and photostabilized V oc of 1.22 V. The resultant monolithic perovskite–perovskite tandem solar cell shows a high V oc of 1.98 V (approaching 80% of the theoretical limit) and a stabilized PCE of 18.5%. The significantly minimized nonideal V oc,loss is better than state‐of‐the‐art silicon–perovskite tandem solar cells, which highlights the prospects of using perovskite–perovskite tandems for solar‐energy generation. It also unlocks opportunities for solar water splitting using hybrid perovskites with solar‐to‐hydrogen efficiencies beyond 15%. High open‐circuit voltage, V oc (1.98 V) and power conversion efficiency, PCE (18.5%) is realized in an ideal bandgap‐matched two‐terminal perovskite–perovskite tandem solar cell via an integrated approach. A fullerene variant, Indene‐C60 bis‐adduct is used to achieve optimized interfacial contact and alleviate hysteresis instabilities in the small‐bandgap subcell. Compositional engineering is employed to realize more highly photostabilized V oc in the large‐bandgap subcell.